EFFECT OF PHARMACOLOGICAL PUPIL DILATION ON INTRAOCULAR LENS POWER CALCULATION IN PATIENTS INDICATED FOR CATARACT SURGERY - Autrata, D; Chrapek, O; Drahorád, S (Ceska a slovenska oftalmologie, 2021)
PURPOSE: To evaluate the influence of pupil dilation on ocular parameters measured by optical biometry and the influence of pupil dilation on intraocular lens (PC IOL) power calculation by using the third-generation (SRK/T) and the fourth-generation (Haigis) formula. METHODS: 40 eyes of patients indicated for cataract surgery were included in this study. Each patient was examined by optical biometer firstly without artificial mydriasis (AM) and then after AM, which was achieved using local application of short-term acting mydriatics. Biometric data were measured by Lenstar LS 900 optical biometer, we recorded axial length of the eye (AL), central corneal thickness (CCT), anterior chamber depth (ACD), lens thickness (LT) and corneal astigmatism and optical power of cornea. These data we measured were used for calculation of the PC IOL optical power using both the SRK/T and the Haigis formula. The target postoperative refraction was set to emmetropia. Statistical analysis was performed for evaluation of influence of AM on each ocular parameter and influence of AM on the recommended PC IOL power calculated by the SRK/T and the Haigis formula. RESULTS: No statistically significant effect of AM on AL, LT and keratometry was demonstrated. On the contrary we demonstrated significant effect on CCT and ACD. No effect of AM on the PC IOL power calculation using the SRK/T formula was proved - the PC IOL optical power before AM and after AM did not differ in any case. When using the Haigis formula for the PC IOL power calculation, the recommended optical power of the PC IOL changed by +0.5 Dpt in 9 eyes, i.e., 22.5 % of the whole group, but statistical analysis did not show this change as statistically significant. CONCLUSION: Pharmacological dilation of the pupil significantly affects some intraocular parameters measured by optical biometer and in the case of using the Haigis formula it can influence recommended power of the PC IOL. Conversely, when using the SRK/T formula, pharmacological dilation of pupil does not affect the recommended PC IOL power.
Keywords: katarakta; anterior chamber depth; nitrooční čočky; Cataract surgery; Humans; Haigis formula; pupila; mydriasis; lidé; keratometry; SRK/T formula; optical biometry; intraocular lens calculation; Lenses, Intraocular; Refraction, Ocular; biometrie; fakoemulzifikace; Biometry; Cataract; refrakce oka; Phacoemulsification; axial length; Pupil